PEMANFAATAN MEDIA MASSA DALAM UPAYA MENINGKATKAN PENERIMAAN SISWA BARU DI ERA GLOBALISASI - Bandawati, Sesi; Anggriani, Dea; Aziz, Nur (Universitas Tanjungpura, 2024)
The use of mass media in the era of globalisation to assist educational institutions in increasing new student admissions. This study aims to examine the use of mass media in an effort to increase new student admissions in the era of globalisation. This research method is a descriptive method with a literature study approach or library research which involves searching for data about various things or variables from notes, books, papers, articles, journals, and others. This library research focuses on the use of mass media in an effort to increase new student admissions in the era of globalisation. The results of the literature study found that when mass media is used as a medium of promotion or marketing of the vision and mission and excellent programmes, the information will be widely spread in a short period of time compared to traditional or conventional promotion. After reviewing several studies that have been analysed, there are those that suggest that mass media is quite influential, especially in new student admissions, especially school websites are an important element that every institution must have. Therefore, in addition to using conventional methods, it turns out that educational institutions need to upgrade the marketing methods for new student admissions using modern methods through mass media, in order to increase the perfect new student admission target.